Can Libya survive as a single State? - George Joffé (L’Année du Maghreb)
Ever since the Qadhafi regime collapsed in late October 2011, the survival of the Libyan state has been opened to increasing question. The causes are manifold; the collapse of the Libyan army in the wake of the NATO-led attacks, the hostility of Britain and France, the roles played by the Gulf states, Turkey and Egypt, and the growth of extremism against the background of the privatised violence of the militias have all contributed towards its impending collapse. Nonetheless, apart from the unifying role played by country’s central bank and national oil company, pressure for preserving the unitary state has been driven by two players from diametrically opposed positions; the United Nations which seeks a new constitution and nationwide elections and the leader of the major militia coalition in the country, Khalifa Haftar, based in Benghazi and now seeking to extend his autocratic control over Tripolitania too. Now Libya is being dragged into a proxy war, involving the UAE and Egypt as opposed to Qatar and Turkey and the regional level and, more globally, Russia, the United States, France and Italy. The ultimate victim, however, could well be the Libyan state!